A Analisis perbandingan sektor keuangan pada rencana strategis bank di Indonesia - Putri, Nurul Fajriyah Hidayat; Aulia, Irma Fitriana; Khatimah, Khusnul (Maliki Interdisciplinary Journal, 2024)
The increasing growth of companies in the financial sector will continue to create management competition for existing financial companies, both bank and non-bank companies. Therefore, to face this competition, it is very important for the company to implement a company strategic plan and then analyze it with competitors. As a result of this comparative analysis, the company can find new ways to plan the company’s direction through updating strategic plans that will be used in the future. The purpose of writing this article is to compare the strategic plans of three financial sector companies. However, the comparisons in this research will be divided according to the company’s environmental segmentation.